When Crime Meets Pandemic: Organized Crimes and Triad Societies’ Activities during COVID-19 Pandemic in Hong Kong - Wei Luk, Bryan Tzu (International Journal of Criminology and Sociology, 2023)
Recent studies suggest that the pandemic has impacted criminal activities and organized crime groups. This article provides a qualitative review of changes in crime rates, patterns, and activities of organized crime groups (specifically, Triads) in Hong Kong. Three specific types of organized crimes with high Triad involvement were selected: serious violent crimes, serious drug-related crimes, and smuggling. After analyzing both official and non-official sources, the results showed that despite the government's stringent control measures that significantly suppressed socio-economic activities during the COVID-19 pandemic, the figures for these selected crimes rose tremendously. Triads' organized criminal activities became more frequent, dangerous, and aggressive, posing a severe threat to Hong Kong's law and order.